Content and specific features of the status of a Constitutional court judge: a theoretical and legal analysis - Kozhakhmetova, С.Г.; Tuleubayeva, Г.Ж.; Kasymbek, А.О. (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2026)
This study examines the theoretical and legal foundations of the legal status of a judge of the Constitutional Court. Particular attention is paid to the constitutional and legal nature of the status of a judge of the constitutional review body, the judge's place within the system of state authority, and the role in ensuring the supremacy of the Constitution and protecting human and civil rights and freedoms. The relevance of the topic is determined by the fact that the Constitutional Court serves as a key institution of constitutional review whose activities are aimed at maintaining the balance between the branches of government, upholding the principles of the rule of law, and strengthening constitutional legality. The purpose of this article is to reveal the content and specific features of the legal status of a Constitutional Court judge, with particular emphasis on a comparative legal analysis of selected national models, specifically the legislation of the Russian Federation and the Republic of Poland. In this regard, the article examines the concept, principal structural elements, and specific characteristics of the legal status of judges of the Constitutional Court of the Republic of Kazakhstan. Particular attention is devoted to such components of legal status as the rights and duties of judges, guarantees of judicial independence, qualification requirements for candidates, legal restrictions and prohibitions, as well as the procedure for termination of judicial powers and the grounds for legal responsibility. The study demonstrates that the legal status of a Constitutional Court judge possesses a unique legal nature, as it is associated not only with the administration of constitutional justice but also with safeguarding the foundations of the constitutional order. A Constitutional Court judge must possess a high level of professional competence, legal culture, independence, and impartiality. Based on the conducted analysis, the article concludes that the legal status of judges of the Constitutional Court of the Republic of Kazakhstan plays a crucial role in ensuring the stability of the constitutional system, strengthening the rule of law, enhancing public confidence in state institutions, and promoting the further development of a democratic state governed by the rule of law.